Identifying and Enhancing the Manageability Component of Salutogenic Architecture in the Psychiatric Ward of Bali Provincial Mental Hospital to Improve Patient Recovery - Made Arya Adiartha; Km. Deddy Endra Prasandya; Pande Putu Dwi Novigga Artha (International Journal of Architecture and Urbanism, 2026)
This study examines the application of the Salutogenic framework in the architectural design of Bali Provincial Mental Hospital’s Bisma ward, focusing on improving mental health recovery through better environmental design. Using a mixed-methods approach, the research evaluates the ward based on the Sense of Coherence (SOC) components”Manageability, Comprehensibility, and Meaningfulness. The findings reveal that the Manageability component, which emphasizes patient control over their environment, scored the lowest, with seven out of eleven criteria falling below 70%. Key issues include centralized nurse stations, inadequate patient monitoring spaces, and poor accessibility for patients with disabilities. To address these gaps, the study provides recommendations such as decentralizing nurse stations, improving safety features without creating a prison-like atmosphere, and enhancing barrier-free accessibility. While Comprehensibility and Meaningfulness scored higher, there is still room for improvement in reducing spatial uncertainty and fostering meaningful engagement. The study’s design recommendations aim to create a more supportive and empowering environment, aligning with Salutogenic principles to enhance patient recovery.